The Effect of Cooking Class on the Cognitive Abilities of Group a Kindergarten Children in Cluster IV Gedangan Sidoarjo District - Syifaul Adhimah; Bachtiar Syaiful Bachri; Miftakhul Jannah (IKIP Mataram, 2023)
This study aims to determine the effect of cooking class activities on the cognitive abilities of group A children in Cluster IV, Gedangan Sidoarjo District. This study uses a quasi-experimental design through a quantitative approach. The experimental design used was nonequivalent control group design. The subjects in this study were the children of group A RA Al Islah Karangbong with a total of 51 children as the experimental group and PAUD Tashwirul Afkar Karangbong with a total of 30 children as the control group. Data analysis techniques in this study used non-parametric statistics with the Mann Whitney Test. The results of this study indicate that